ANTIBACTERIAL ACTIVITY TEST OF STRAWBERRY (FRAGARIA × ANANASSA) FRUIT EXTRACT AGAINST THE GROWTH OF STREPTOCOCCUS SANGUINIS - Pascharia, Theresia Imelda; Sugiaman, Vinna Kurniawati; Dwiarie, Theodora Adhisty (Indonesian Journal of Dentistry, 2025)
Background: Strawberry (Fragaria × ananassa) is a natural substance known to reduce dental plaque formation due to its content of bioactive compounds, including saponins, tannins, alkaloids, steroids, and triterpenoids. This study aimed to evaluate the antibacterial activity of strawberry fruit extract, prepared using 70% ethanol as a solvent through maceration to produce a concentrated liquid extract, against Streptococcus sanguinis—a bacterium associated with plaque formation.Method: The study employed microdilution and agar dilution methods. Antibacterial activity was assessed through the determination of the Minimum Inhibitory Concentration (MIC), indicated by a marked decrease in optical density, and the Minimum Bactericidal Concentration (MBC), determined by the absence of bacterial colony growth.Outcome: Results showed that the MIC of the strawberry extract against S. sanguinis was 6.25%, while the MBC was 50%.Conclusion: These findings indicate that strawberry extract (Fragaria × ananassa) exhibits both inhibitory and bactericidal activity against the growth of Streptococcus sanguinis.